A Kasus Langka: Intususepsi Pada Orang Dewasa - Dona, Adma Hayani; Pramudya, Ricky; Parinding, Imanuel Taba (CV. Jasa Sukses Abadi, 2024)
Intussusception is defined as the invagination of one segment of intestine into the next. Unlike children, intussusception in adults is rare. The incidence of intussusception in adults is around 1%-5% of intestinal obstruction with an average age of 50 years. Compared with intussusception in children, intussusception in adults is different because 90% of cases are complications of pathological starting points, including polyps, carcinoma, strictures, adhesions, and Meckel's diverticulum. Meanwhile, the incidence of idiopathic intussusception is around 10% of cases. A 39-year-old woman with a history of right lower abdominal pain for 3 days came to the emergency department accompanied by vomiting, no bowel movements and a history of abdominal massage. Physical examination found a positive Mc Burney sign, a sausage-like mass was palpable, abdominal ultrasonography showed a doughnut sign and an impression of ileo-caecal intussusception. The patient underwent exploratory laparotomy and appendectomy. During the operation, ileocaecal invagination into the ascending colon was seen, then a milking procedure was performed. The patient was discharged in stable condition on the fifth day of hospitalization. Management of intussusception depends on the part of the intestine involved. Reduction of acute intussusception is an emergency procedure and should be performed immediately after diagnosis in preparation for possible surgery. Management can be done operatively or non-operatively. Resection of the intestine is the final choice if the intestinal viability is compromised or there are pathological points. Early diagnosis and timely intervention greatly affect the patient's prognosis.